The Influence of HIV/AIDS Prevention Education By Using Lecture Method on the Level of Adolescents Knowledge at SMP Hasanka Boarding School Palangka Raya - Windy Ratih; Mariaty A. Sangkai; Anggreni Ade Putri (Universitas Ibn Khaldun Bogor, 2026)
Adolescents are an age group that is vulnerable to HIV/AIDS transmission due to a lack of knowledge about transmission and prevention. This study aims to determine the effect of HIV/AIDS education using the lecture method on the level of understanding of adolescents in preventing HIV/AIDS at SMP Hasanka Boarding School Palangka Raya. The study employed a pre-experimental design with a one-group pretest-posttest design. The sample consisted of 79 students in grades VII and VIII who were selected using a proportionate stratified random sampling technique. The instrument was an HIV/AIDS knowledge questionnaire given before and after education. Education was conducted through the lecture method, utilizing PowerPoint and poster media. Data analysis used the Wilcoxon test. The results showed a significant increase in adolescent knowledge after education (p < 0.05).